Study of the Effects of Monacolin K and Other Constituents of Red Yeast Rice on Obesity, Insulin-Resistance, Hyperlipidemia, and Nonalcoholic Steatohepatitis Using a Mouse Model of Metabolic Syndrome - Fujimoto, Makoto (Hindawi Publishing Corporation, 2012)
Purpose. Nonalcoholic fatty liver disease (NAFLD) is a progressive and intractable disease associated with metabolic syndrome. Red yeast rice (RYR) contains monacolin K, a potent inhibitor of HMG-CoA reductase, and its consumption decreases cholesterol and triglyceride levels. We examined the efficacy of RYR constituents using a novel metabolic syndrome-NAFLD mouse model (MSG mice). Methods. Two types of RYR grown under different culture conditions were used. 1P-DU contained only 0.002 g/100 g of monacolin K, whereas 3P-D1 contained 0.131 g/100 g. MSG mice were divided into three groups: control (C) group fed standard food, RYR-C group fed standard food with 1% 1P-DU, and RYR-M group fed standard food with 1% 3P-D1. Mice were examined from 12 to 24 weeks of age. Results. Serum insulin, leptin, and liver damage as well as macrophage aggregation in visceral fat in RYR-C and RYR-M groups were lower than those in C group. The serum adiponectin levels in RYR-C group were significantly higher than those in RYR-M and C groups. Conclusions. RYR was effective against obesity-related inflammation, insulin resistance, and NAFLD in MSG mice irrespective of monacolin K levels. GABA and various peptides produced during fermentation were determined as the active constituents of RYR.